2015
DOI: 10.1016/j.jarmac.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Updating and working memory training: Immediate improvement, long-term maintenance, and generalisability to non-trained tasks.

Abstract: Despite the popularity of working memory (WM) and updating training, recent reviews have questioned their efficacy. We evaluated a computer-based training programme based on the Running Span and Keep Track paradigms. We assigned 111 7-year-olds with poor WM and mathematical performances to updating training, one of the two control groups, or a fourth group, who were administered Cogmed, a commercially available programme. At the immediate posttest, updating training produced only marginal improvements relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 50 publications
2
28
2
2
Order By: Relevance
“…Instead, the lack of transfer to executive functions suggests that any far transfer to mathematical skills would not be expected. The fact that we found no far transfer to mathematical skills or to classroom engagement adds to a growing literature demonstrating that cognitive training targeting executive functions does not transfer to children's academic skills (Ang, Lee, Cheam, Poon, & Koh, 2015;Dunning, Holmes, & Gathercole, 2013). However, the lack of near transfer to untrained measures of working memory was unexpected, particularly because in a smaller scale study with mid-SES children this training program improved working memory.…”
Section: Discussioncontrasting
confidence: 46%
“…Instead, the lack of transfer to executive functions suggests that any far transfer to mathematical skills would not be expected. The fact that we found no far transfer to mathematical skills or to classroom engagement adds to a growing literature demonstrating that cognitive training targeting executive functions does not transfer to children's academic skills (Ang, Lee, Cheam, Poon, & Koh, 2015;Dunning, Holmes, & Gathercole, 2013). However, the lack of near transfer to untrained measures of working memory was unexpected, particularly because in a smaller scale study with mid-SES children this training program improved working memory.…”
Section: Discussioncontrasting
confidence: 46%
“…By contrast, Rapport, Orban, Kofler, and Friedman's (2013) meta-analysis reported little or no evidence of amelioration in academic achievement in children with ADHD after WM training. In line with Rapport et al's (2013) results, Redick et al's (2015) review showed that WM training did not provide any benefit to academic performance in children with ADHD (e.g., Chacko et al, 2014) and poor WM (e.g., Ang, Lee, Cheam, Poon, & Koh, 2015), or in typical developing children (e.g., Rode, Robson, Purviance, Geary, & Mayr, 2014).…”
Section: Working Memory Training In Childrenmentioning
confidence: 81%
“…These results have been replicated in children with attention-deficit/hyperactivity disorder (Beck, Hanson, Puffenberger, Benninger, & Benninger, 2010;Chacko et al, 2013), low IQ (Kronenberger et al, 2011), hearing impairments (Van der Molen et al, 2010), low-level language abilities (Holmes et al, 2015), and poor WM (Holmes et al, 2010). Recent reviews of this literature (B. S. Gibson, Gondoli, Johnson, Steeger, & Morrissey, 2012;Shipstead, Redick, & Engle, 2012) and the results of a number of recent studies (Ang, Lee, Cheam, Poon, & Koh, 2015; van der Donk, Hiemstra-Beernink, Tjeenk-Kalff, van der Leij, & Lindauer, 2015;van Dongen-Boomsma, Vollebregt, Buitelaar, & Slaats-Willemse, 2014;Yu, Li, Liu, An, & Liu, 2015) unfortunately have cast some doubt on the idea that WM training really improves WM capacity. In addition, we know of no experimental evidence suggesting that Cogmed training generalizes to changes in sentence comprehension.…”
Section: Phase 3: Experimental Studiesmentioning
confidence: 86%